2015
DOI: 10.1038/srep12888
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-genome sequencing reveals the effect of vaccination on the evolution of Bordetella pertussis

Abstract: Herd immunity can potentially induce a change of circulating viruses. However, it remains largely unknown that how bacterial pathogens adapt to vaccination. In this study, Bordetella pertussis, the causative agent of whooping cough, was selected as an example to explore possible effect of vaccination on the bacterial pathogen. We sequenced and analysed the complete genomes of 40 B. pertussis strains from Finland and China, as well as 11 previously sequenced strains from the Netherlands, where different vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
4
37
0
1
Order By: Relevance
“…Yet B. pertussis persists, and pertussis disease has resurged, in part due to genetic divergence of circulating strains. Although reference strains used for vaccine production vary (1), growing evidence suggests that B. pertussis is evolving under vaccine-driven selection (25). Here, we report the complete genome sequences of four strains (134, 509, 6229, 25525) used by Serum Institute of India to manufacture whole-cell pertussis vaccines.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Yet B. pertussis persists, and pertussis disease has resurged, in part due to genetic divergence of circulating strains. Although reference strains used for vaccine production vary (1), growing evidence suggests that B. pertussis is evolving under vaccine-driven selection (25). Here, we report the complete genome sequences of four strains (134, 509, 6229, 25525) used by Serum Institute of India to manufacture whole-cell pertussis vaccines.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The global emergence of Prn deficiency is well documented (13,14) but, although likely vaccine driven (15), does not appear to impact the effectiveness of aP vaccines (16). Together, such genetic shifts illustrate how circulating B. pertussis has significantly diverged from vaccine reference strains since widespread vaccine introduction, which many researchers have attributed to vaccine-driven immune selection (4,10,15,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Previous genomic studies have identified only a few mutations within a limited number of genes, each of which have quickly spread throughout the circulating population with little evidence of geographic restriction (5,11). These mutations have occurred in genes encoding immunogenic proteins, most notably those for antigens in currently used acellular pertussis vaccines, such as genes for pertussis toxin (ptxA and the promoter region ptxP) and fimbriae (fimH), leading many to conclude that they result from vaccine-driven selection (5,(12)(13)(14)(15). Although sequence diversity has also been observed in the vaccine immunogen pertactin (Prn), the circulating isolates recovered in the United States have become predominantly Prn deficient in recent years by one of at least 16 different mutations to the prn gene (16).…”
mentioning
confidence: 99%